The spatial structure of Antarctic biodiversity. Issue 2 (1st May 2014) - Convey, Peter; Chown, Steven L.; Clarke, Andrew; Barnes, David K. A.; Bokhorst, Stef; Cummings, Vonda; Ducklow, Hugh W.; Frati, Francesco; Green, T. G. Allan; Gordon, Shulamit; Griffiths, Huw J.; Howard-Williams, Clive; et al.
Abstract : Patterns of environmental spatial structure lie at the heart of the most fundamental and familiar patterns of diversity on Earth. Antarctica contains some of the strongest environmental gradients on the planet and therefore provides an ideal study ground to test hypotheses on the relevance of environmental variability for biodiversity. To answer the pivotal question, "How does spatial variation in physical and biological environmental properties across the Antarctic drive biodiversity?" we have synthesized current knowledge on environmental variability across terrestrial, freshwater, and marine Antarctic biomes and related this to the observed biotic patterns. The most important physical driver of Antarctic terrestrial communities is the availability of liquid water, itself driven by solar irradiance intensity. Patterns of biota distribution are further strongly influenced by the historical development of any given location or region, and by geographical barriers. In freshwater ecosystems, free water is also crucial, with further important influences from salinity, nutrient availability, oxygenation, and characteristics of ice cover and extent. In the marine biome there does not appear to be one major driving force, with the exception of the oceanographic boundary of the Polar Front. At smaller spatial scales, ice cover, ice scour, and salinity gradients are clearly important determinants of diversity at habitat and community level. Stochastic and extreme events remain an important driving force in all environments, particularly in the context of local extinction and colonization or recolonization, as well as that of temporal environmental variability. Our synthesis demonstrates that the Antarctic continent and surrounding oceans provide an ideal study ground to develop new biogeographical models, including life history and physiological traits, and to address questions regarding biological responses to environmental variability and change.